Penguatan Soft Skill Dan Personal Branding Untuk Kesuksesan Karier Desainer SMK Ki Hajar Dewantoro - Misky, Fatma; Reza, Yuliana Choerul; Rusmiati, Debi (Universitas Budi Luhur, 2025)
his community service program aims to strengthen personal branding competencies of Visual Communication Design (VCD) students as preparation for entering the creative industry. The rapid growth of the creative sector requires vocational graduates to possess not only technical design skills but also soft skills such as communication, self-confidence, and professional self-image. Initial observations at Ki Hajar Dewantoro Vocational High School revealed limited understanding of personal branding and lack of structured digital portfolios among students. The program was implemented through interactive seminars, hands-on workshops on personal branding kits (creative CVs and digital portfolios), and mentoring sessions focusing on soft skill development. The results indicate improved student awareness of personal branding, the creation of personal digital portfolios, and enhanced confidence in self-presentation. This activity contributes to improving students’ career readiness and supports sustainable development of vocational education in the creative industry.